Exploring the link between innovation and digital trade exports: Cross-country firm-level evidence - Phuong, Do Manh (Edelweiss Applied Science and Technology, 2026)
This study examines the relationship between firm-level innovation and participation in digital trade exports, with particular attention to heterogeneity across firm sizes. Using cross-country firm-level data from the World Bank Enterprise Surveys covering 94 countries during 2022–2025, the analysis focuses on manufacturing firms. Innovation is measured using both input indicators (R&D investment) and output indicators (new products and improved processes). Probit and instrumental variable (IV) estimations are employed to address potential endogeneity, with sector–location average innovation used as an instrument. The results show that innovation significantly increases the likelihood of engaging in digital trade exports. Innovative firms are more likely to export digitally, even after controlling for endogeneity. However, the effect is heterogeneous: innovation has a strong positive impact for small and medium-sized enterprises (SMEs), while the effect is weaker or negative for large firms. Access to foreign technology, internet connectivity, and financial resources further shape digital export participation. Innovation plays a critical role in enabling firms to participate in digital trade, particularly among SMEs. The findings suggest that policies promoting R&D, digital infrastructure, and financial access, especially for SMEs, can foster more inclusive participation in global digital markets.